2010
DOI: 10.1111/j.1365-2214.2010.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Are family‐centred principles, functional goal setting and transition planning evident in therapy services for children with cerebral palsy?

Abstract: Lack of formal processes for delivery of family-centred service, goal-setting and co-ordination between children's programmes may result in inequitable opportunities for families to participate in their children's rehabilitation despite attending the same programme. Standardized programme processes and policies may provide a starting point to ensure that all families have equitable opportunities to participate in their child's rehabilitation programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 25 publications
2
66
0
Order By: Relevance
“…This adaption process, as described by Piggot and colleagues () and later by Rentinck and colleagues (), found that parent adaptation was related to change in their child's development and in stages of family life over time. Similarly, Darrah and colleagues () also noted that preferences of families may change over time.…”
Section: Discussionmentioning
confidence: 90%
“…This adaption process, as described by Piggot and colleagues () and later by Rentinck and colleagues (), found that parent adaptation was related to change in their child's development and in stages of family life over time. Similarly, Darrah and colleagues () also noted that preferences of families may change over time.…”
Section: Discussionmentioning
confidence: 90%
“…; Darrah et al . ), full implementation of these concepts is difficult to achieve (Bailey et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A stronger view of the hemodialysis unit as child-focused could be expanded to include that also of family-centred principles that includes collaboration, information-sharing and recognition and respect for the uniqueness of each family (Darrah, Wiart, Magill-Evans, Ray & Andersen, 2010). In their study that investigated the practices of family-centred service in pediatric rehabilitation programmes for children with cerebral palsy in Alberta, Canada, Darrah, et al (2010) found that although some programmes espoused a commitment to family-centred care, indicators of this approach and formal processes for its delivery often were deficient.…”
Section: Implications For Health Care Practices and Policymentioning
confidence: 99%
“…In their study that investigated the practices of family-centred service in pediatric rehabilitation programmes for children with cerebral palsy in Alberta, Canada, Darrah, et al (2010) found that although some programmes espoused a commitment to family-centred care, indicators of this approach and formal processes for its delivery often were deficient.…”
Section: Implications For Health Care Practices and Policymentioning
confidence: 99%